2020
DOI: 10.1021/acs.langmuir.0c02537
|View full text |Cite
|
Sign up to set email alerts
|

Davydov Split Aggregates of Cyanine Dyes on Self-Assembled Nanotubes

Abstract: The Davydov splitting of dye aggregates represents unique molecular excitons. In this paper, we report the formation of Davydov split aggregates of 3,3′-diethylthiacarbocyanine iodide (DiSC2 (3)) and 3,3′-diethylthiadicarbocyanine iodide (DiSC2 (5)) templated by the helical nanotubes of lithocholic acid (LCA). The templated Davydiv split aggregates show a strong J-band and a weak H-band in the adsorption spectra. As the LCA helical nanotubes transform into a straight shape, the relative intensities of the J-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…41 Fang and co-workers have reported the formation of dye aggregates (J-and H-aggregates) from the co-assembly of LCA with 3,3′-diethylthiadicarbocyanine iodide dyes (DiSC 2 (3) and DiSC 2 (5)) in aqueous ammonia solution. 42,46 However, so far, no detailed investigation on the exciton fluorescence properties of the LCA-templated dye aggregates has been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Fang and co-workers have reported the formation of dye aggregates (J-and H-aggregates) from the co-assembly of LCA with 3,3′-diethylthiadicarbocyanine iodide dyes (DiSC 2 (3) and DiSC 2 (5)) in aqueous ammonia solution. 42,46 However, so far, no detailed investigation on the exciton fluorescence properties of the LCA-templated dye aggregates has been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The LCA has been chosen in this work because of its unique ability to self-assemble into highly monodisperse nanotubes through helical ribbon formation in ammonia solution. , In the past, LCA nanotubes have been utilized for the formation of supramolecular assemblies with dyes, proteins, and heavy metal ions . Fang and co-workers have reported the formation of dye aggregates (J- and H-aggregates) from the co-assembly of LCA with 3,3′-diethylthiadicarbocyanine iodide dyes (DiSC 2 (3) and DiSC 2 (5)) in aqueous ammonia solution. , However, so far, no detailed investigation on the exciton fluorescence properties of the LCA-templated dye aggregates has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…27 In a previous study, we showed that DiSC 2 (5) in 15% ammonia solution formed both H- and J-aggregates. 28 Interestingly, 1 mM DiSC 2 (5) in 30% ammonia solution only formed H-aggregates with the H-band at 450 nm (Fig. 2b).…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, the H-aggregate tubes showed the predominance of the H 1 -band over the H 2 -band, while the H-aggregate vesicles showed the predominance of the H 2 -band over the H 1band. The inclination angle (θ) of DiSC 2 (3) molecules in Haggregate vesicles and tubes could be calculated from the oscillation strength of the two Davydov components (H 1 -and H 2 -bands) with the equation 32,33 tan…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the H-aggregate tubes showed the predominance of the H 1 -band over the H 2 -band, while the H-aggregate vesicles showed the predominance of the H 2 -band over the H 1 -band. The inclination angle (θ) of DiSC 2 (3) molecules in H-aggregate vesicles and tubes could be calculated from the oscillation strength of the two Davydov components (H 1 - and H 2 -bands) with the equation , , where A H1 ‑ band and A H2 ‑ band are the oscillation strengths of the H 1 -band and the H 2 -band, respectively. The ratio of A H1 ‑ band / A H2 ‑ band is proportional to the ratio of the areas under the H 1 -band and the H 2 -band in adsorption spectra.…”
Section: Results and Discussionmentioning
confidence: 99%